Overcoming platinum-acquired resistance in ovarian cancer patient-derived xenografts. (June 2019) - Ricci, Francesca; Brunelli, Laura; Affatato, Roberta; Chilà, Rosaria; Verza, Martina; Indraccolo, Stefano; Falcetta, Francesca; Fratelli, Maddalena; Fruscio, Robert; Pastorelli, Roberta; Damia, Giovanna
Background: Epithelial ovarian cancer is the most lethal gynecological cancer and the high mortality is due to the frequent presentation at advanced stage, and to primary or acquired resistance to platinum-based therapy. Methods: We developed three new models of ovarian cancer patient-derived xenografts (ovarian PDXs) resistant to cisplatin (cDDP) after multiple in vivo drug treatments. By different and complementary approaches based on integrated metabolomics (both targeted and untargeted mass spectrometry-based techniques), gene expression, and functional assays (Seahorse technology) we analyzed and compared the tumor metabolic profile in each sensitive and their corresponding cDDP-resistant PDXs. Results: We found that cDDP-sensitive and -resistant PDXs have a different metabolic asset. In particular, we found, through metabolomic and gene expression approaches, that glycolysis, tricarboxylic acid cycle and urea cycle pathways were deregulated in resistant versus sensitive PDXs. In addition, we observed that oxygen consumption rate and mitochondrial respiration were higher in resistant PDXs than in sensitive PDXs under acute stress conditions. An increased oxidative phosphorylation in cDDP-resistant sublines led us to hypothesize that its interference could be of therapeutic value. Indeed, in vivo treatment of metformin and cDDP was able to partially reverse platinum resistance. Conclusions: Our data strongly reinforce the idea that the development of acquired cDDP resistance in ovarian cancer can bring about a rewiring of tumor metabolism, and that this might be exploited therapeutically.